Philosophy of values and its epistemological representations in industrial product design (Al-Academy, 2022)
The research dealt with the concepts of the philosophy of values ​​and its epistemological variables according to specific propositions represented in their scientific approaches to value theory in the field of industrial design. As the epistemological propositions of the theory of values ​​were dealt with based on the epistemological fields that dealt with the concept and what values ​​are, starting with the modernist propositions and postmodern, passing through the propositions of sociological and psychological thought, which was a prelude to extracting the concepts of value theory and adopting it in the field of industrial product design. The epistemological approaches to value theory in industrial product design were represented in eleven value orientations represented by values: ethical, ecological, functional, use, semantic, brand, self-expression, cultural, rituals, belonging, identity and aesthetic values. After discussing the types of these epistemological approaches to the theory of values ​​in the design of the industrial product according to the nature of each type of value, a number of conclusions were reached, which represented an objective analysis of the ways in which the theoretical concepts of the philosophy of values ​​were transformed into theoretical systems that can be applicable in industrial product design.